7(6-x)=5x-2(5x-6)

Simple and best practice solution for 7(6-x)=5x-2(5x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6-x)=5x-2(5x-6) equation:


Simplifying
7(6 + -1x) = 5x + -2(5x + -6)
(6 * 7 + -1x * 7) = 5x + -2(5x + -6)
(42 + -7x) = 5x + -2(5x + -6)

Reorder the terms:
42 + -7x = 5x + -2(-6 + 5x)
42 + -7x = 5x + (-6 * -2 + 5x * -2)
42 + -7x = 5x + (12 + -10x)

Reorder the terms:
42 + -7x = 12 + 5x + -10x

Combine like terms: 5x + -10x = -5x
42 + -7x = 12 + -5x

Solving
42 + -7x = 12 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
42 + -7x + 5x = 12 + -5x + 5x

Combine like terms: -7x + 5x = -2x
42 + -2x = 12 + -5x + 5x

Combine like terms: -5x + 5x = 0
42 + -2x = 12 + 0
42 + -2x = 12

Add '-42' to each side of the equation.
42 + -42 + -2x = 12 + -42

Combine like terms: 42 + -42 = 0
0 + -2x = 12 + -42
-2x = 12 + -42

Combine like terms: 12 + -42 = -30
-2x = -30

Divide each side by '-2'.
x = 15

Simplifying
x = 15

See similar equations:

| (v+5)(v-2)=0 | | 8(4)=w(7)-w(3) | | 5r+-9=-7r+6 | | -1(3x+1)=-7 | | 4(2x+b)-3(4-3c)=5b+6x | | (2x-3)/(-1)=(1-4x)/2 | | 27y-18= | | 5r^2-22r+21=0 | | 2x-1/21=x-5/24 | | 5n+5=2p | | 50=3x+5x | | 180=2(4y-15)+7 | | 7(t-8)+50=10t+14+2t | | 8n-6+1n+10= | | .1(40x)-1/2(16) | | 3(x-7)+2x=10 | | 3(x+2)=0.55(2x+3) | | 180x(2x+8)= | | X+.05=2.10 | | (-3g)-(-1)= | | 4u+9=69 | | 5q+14=72q | | 2q+375=857 | | 3(x+13)=7x-9 | | 7(t-8)+50=10t+15+2t | | 8e-(-2)=6 | | 4/9x^2=3 | | y-1/3=1/6 | | 9+5r+5r+2r= | | 30=1x-80 | | -1.4-2.7= | | 9(2x+3y)= |

Equations solver categories